Pengaruh Bauran Pemasaran (Produk, Harga, Tempat, Promosi) Terhadap Loyalitas Konsumen Pada Kedai Kopi Matada Di Brebes - Syafa'at, Andi; Amron, Amron; Wismantoro, Yohan; Setiawan, Aries (Politeknik Negeri Ambon, 2024)
The marketing mix is a of factors that a firm my manipulate in order toachievethe desired level of sales in its target market. In other words, the four Ps stand for product, pricing, place and promotion. This study used a statistical series technique with a population of 120 Matada coffe shop customers in Brebes. The studyâ€™s participants were Brebes residents who had made purchasesat Matada coffe shops. The purposive sampling method was used. Statistical tests, classical assumption tests, and linear regression tests are used to evaluate data. These statistics may be analyzed with IMB SPSS 24 sofware. The purpose of this study was to determine the influence of product, pricing, locationÂ and market impact consumer loyalty t Matada Coffe Shops in Brebes City. The conclusion of this study show that product, pricing, and promotion all have positive and substantial impact. While the location has a negative and minor impact. Keywords: product; price; place; promotion dan consumer loyalty